Fit, misfit, and design: JOD studies that touch reality - Richard M. Burton (Journal of Organization Design, 2020)
Fit is both conceptually and empirically at the heart of our science in organization design. Illustratively, Joseph (2018) found in a text analysis of abstracts in the Journal of Organization Design (JOD) that fit was the most prevalent topic in articles published since the journal's founding. Fit is synonymous with words such as alignment, match, integration, and coordination. Alternatively, misfits are synonymous with misalignments, mismatches, gaps, and undesired properties. In this commentary, I take a less formal approach and review all of the JOD articles to find out how the concept of fit is used in these papers. All the articles, whether or not they use the term fit, address the question of how we get the elements of an organization to work together to meet its goals; that is fit.
Keywords: 650